The black stallion - Farley, Walter, 1915-1989. (New York : Bullseye Books : Alfred A. Knopf, 1991)
Young Alec Ramsay is shipwrecked on a desert island with a horse destined to play an important part in his life. Following their rescue their adventure continues in America.
Keywords: Horses -- Juvenile fiction; Farley, Walter, -- 1915-1989.; Horses -- Fiction